Combination therapy of ursodeoxycholic acid and budesonide for PBC–AIH overlap syndrome: a meta-analysis - Zhang H; Yang J; Zhu R; Zheng Y; Zhou Y; Dai W; Wang F; Chen K; Li J; Wang C; Li S; Liu T; et al. (Dove Medical Press, 2015)
Huawei Zhang,1,2,* Jing Yang,1,* Rong Zhu,1,3 Yuanyuan Zheng,1 Yuqing Zhou,1,2 Weiqi Dai,1 Fan Wang,1 Kan Chen,1 Jingjing Li,1 Chengfen Wang,1 Sainan Li,1 Tong Liu,1 Huerxidan Abudumijiti,1 Zheng Zhou,1,3 Jianrong Wang,1,3 Wenxia Lu,1,3 Junshan Wang,1 Yujing Xia,1 Yingqun Zhou,1 Jie Lu,1 Chuanyong Guo1 1Department of Gastroenterology, Shanghai Tenth People’s Hospital, Tongji University School of Medicine, Shanghai, 2The First Affiliated Hospital of Soochow University, Suzhou, 3The First Clinical Medical College of Nanjing Medical University, Nanjing, People’s Republic of China *These authors contributed equally to this work and should be considered co-first authors Abstract: In this study, a meta-analysis of randomized controlled trials comparing ursodeoxycholic acid (UDCA) monotherapy with combination therapies utilizing UDCA and budesonide was performed. We found that combination therapy with UDCA and budesonide was more effective than UDCA monotherapy for primary biliary cirrhosis–autoimmune hepatitis overlap syndrome. Moreover, compared to prednisone, budesonide has fewer side effects. Keywords: meta-analysis, UDCA, budesonide, combination therapy, PBC–AIH overlap syndrome